Exploring the Role of Geographic Information Systems in Modern Data Analysis - Yadav, Ankur (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2025)
Geographic Information Systems (GIS) have become integral in the realm of modern data analysis, offering valuable tools for spatial data collection, visualization, and interpretation. This review examines the evolving role of GIS in various fields, highlighting its impact on industries such as urban planning, environmental management, disaster response, and healthcare. We explore the key features of GIS, including data acquisition, spatial analysis, and mapping technologies, and discuss how these systems are transforming data-driven decision-making. The article also addresses the challenges faced by GIS professionals, such as data quality, system integration, and the need for advanced analytical techniques. Finally, we look at the future of GIS, focusing on emerging trends like cloud computing, machine learning, and real-time data processing, which are shaping the future of spatial data analysis.